Effect of integrated nutrient management on plant growth and yield parameter of strawberry (Fragaria x ananassa Duch.) Var. Chandlar (International Journal of Food and Nutritional Sciences, 2021)
The experiment was carried out at Agriculture Research Farm of Rama University, Mandhana,Kanpur, U.P, India, during October 2021-2022 to investigate the effect of integrated nutrientmanagement on plant growth, & yield parameter of strawberry (Fragaria x ananassa Duch.)var